Military and political aspects of one of the problems of the modern power industry - Gurevich, V. (Електротехніка і електромеханіка, 2015)
The problem of Intentional Destructive Electromagnetic Impacts (IDEI) on power systems has become recently more and more
actual in connection with two modern trends: the extension of using microelectronics and microprocessor-based devices and systems in electric power industry – on the one hand, and the intensive design of special equipment for distance destruction of electronic devices and systems – with another. The most powerful method for such destruction is the High-altitude Electromagnetic
Pulse (HEMP) as a result of a high-altitude nuclear explosion. The history of experimental high-altitude nuclear explosions has
been known now for over half a century. During this time quite a few scientific articles and books presenting details of this phenomenon and measures of protection from it have been published. In view of this fact, it would be possible to assume that the
problem of protection against HEMP has been solved for a long time and modern power systems are well protected from this phenomenon. However the research performed by the author displays that actually it has not and for the past decades in one country
of the world, at least, no practical measures have been taken for the protection of the national infrastructures against HEMP and
all action has been restricted only to writing reports, recommendations and guidelines. In the paper the reasons for such situation
(in particular, political and military aspects of the problem) are analyzed. Проблема преднамеренных дистанционных деструктивных воздействий (ПДДВ) на энергетические системы становится в последнее время все более и более актуальной в связи с двумя современными тенденциями: расширением использования микроэлектроники и устройств на основе микропроцессоров в электроэнергетике – с одной стороны, и
успехами, достигнутыми в разработке специальных видов оружия, предназначенных для дистанционного поражения
электронных устройств – с другой. Самый мощный метод дистанционного поражения электроники – электромагнитный импульс высотного ядерного взрыва (ЭМИ ЯВ). История экспериментальных высотных ядерных взрывов насчитывает половину столетия. За это время было опубликовано множество научных статей, книг, отчетов, подробно описывающих все детали этого процесса и меры защиты от него. В связи с этим, можно было бы предположить, что проблема защиты от ЭМИ ЯВ была за эти десятилетия успешно решена и современные электроэнергетические системы хорошо защищены от этого явления. Однако, исследование, выполненное автором, показывает,
что ни в одной стране мира до сих пор не были предприняты никакие практические меры защиты национальных
инфраструктур от ЭМИ ЯВ и все действия были ограничены только докладами, отчетами, рекомендациями. В данной статье проанализированы причины такой ситуации (в частности, политические и военные аспекты проблемы).